Perkembangan Moral Anak Usia Dini Menurut Piaget: Teori Dan Praktik - Khofifa Juliana; Maganti Sitorus (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Early childhood moral development is an important focus in early childhood education and character building. Jean Piaget is a central figure in the psychology of child moral development, with a theory of stages of moral development that is still used today. This article aims to examine the moral development of early childhood based on Piaget's theory and its practical implications in the context of child education. This study uses a literature study method with qualitative analysis of the latest sources from books, journals, and expert opinions. The results of the study indicate that early childhood is at a heteronomous moral stage, where moral understanding is still influenced by external authorities and rules that are considered absolute. In practice, it is important for educators and parents to guide children through social experiences and moral discussions to reach the autonomous moral stage.